عبدالستار دلوی کی "علی سردار جعفری، شخص، شاعر اور ادیب" : ایک تجزیاتی مطالعہ: An analysis of "Ali Sardar Jafri, Person, Poet and Writer" by Abdul Sattar Dalvi (Al-Qamar, 2023)
Abdul Sattar Dalvi enjoys a remarkable position in Urdu language and literature, research and criticism and in translation and linguistics. He devoted all his life to teach in different universities of the world. He is admired due to his intellectual and literary abilities not only in India but in Pakistan also. His literary master piece “Do Zubanain Do Adab (Urdu Hindi kay Tanazur Main)” is a part of the syllabus of Ph.D. Urdu in various universities of Pakistan. Progressive movement produced many sincere, able, intellectual and honest literary personalities e.g., poets, fiction and prose writers and critics. A prominent name among them was Ali Sardar Jafri. Abdul Sattar Dalvi was well aware of the status of his multifaceted personality, understanding his position and status he saved various articles, written an him, from the hands of the time. In this research work he has presented the articles of eminent writers on the personality, poetry and prose of Ali Sardar Jafri as evidence. This research article is an analysis of Abdul Sattar Dalvi’s work on Ali Sardar Jafri.
Keywords: Research and Criticism; Linguistics Progressive movement; Multifaceted; Masterpiece; Literary and intellectual personality